TLR9 deficiency promotes bone resorption and induces IL-18 expression upon zoledronate treatment - Närhi, Lauri (My University, 2022)
The aim of this study was to determine the effects of TLR9 deficiency on zoledronate-induced inflammation and bone formation. TLR9 is an intracellular DNA receptor expressed in innate immune system cells. Zoledronate is a medicine used to treat bone loss caused by osteoporosis. Zoledronate has effects on bone-resorbing osteoclasts as well as on bone-building osteoblasts. It has also been found in previous studies that zoledronate has a pro-inflammatory effect on several cytokines. TLR9 has been shown to have an influence on the effects of zoledronate, but there is very limited research on the relationship between TLR9 and zoledronate. The data included 24 mice. 12 of these were TLR9 knockout mice that had the lack of exon 1 in TLR9 gene and did not produce functional TLR9 protein. The other 12 mice were wild type mice from the same strain. Of both groups, 6 mice were treated once a week with a dose of zoledronate, and 6 mice were treated with vehicle. The mice were euthanized after 5 weeks. Kidneys, lungs, livers, spleens, and tibiae were dissected and stained for histological analysis. Femurs were imaged with microtomography and analyzed. Blood samples were collected at sacrifice by cardiac puncture. Cytokine concentrations in plasma were analyzed with an immunoassay. We observed that TLR9 deficiency prevented bone formation upon zoledronate treatment. We also found that TLR9 deficiency increased IL-18 expression. The role of TLR9 in N-BP-induced inflammation remains an important subject of research.
Keywords: zoledronate, TLR9